Embedded systems design - Heath, Steve (Oxford ; Boston : Newnes, 2003)
Key Features A practical introduction to the hottest topic in modern electronics design Covers hardware, interfacing and programming in one book New material on Embedded Linux for embedded internet systems Description In this new edition the latest ARM processors and other hardware developments are fully covered along with new sections on Embedded Linux and the new freeware operating system eCOS. The hot topic of embedded systems and the internet is also introduced. In addition a fascinating new case study explores how embedded systems can be developed and experimented with using nothing more than a standard PC. Readership Embedded systems engineers / programmers, electronic engineers, control systems engineers, students of electronic and software engineering.
WHAT IS AN EMBEDDED SYSTEM? -- MEMORY SYSTEMS -- BASIC PERIPHERALS -- INTERFACING TO THE ANALOGUE WORLD -- INTERRUPTS AND EXCEPTIONS -- REAL-TIME OPERATING SYSTEMS -- WRITING SOFTWARE FOR EMBEDDED SYSTEMS -- EMULATION AND DEBUGGING TECHNIQUES -- BUFFERING AND OTHER DATA STRUCTURES -- MEMORY AND PERFORMANCE TRADE-OFFS -- SOFTWARE EXAMPLES -- DESIGN EXAMPLES -- REAL-TIME WITHOUT A RTOS
Includes index.
1
Keywords: CIT; Electronics; Embedded computer systems -- Design and construction